A Rare Case of Perinatal Hypophosphatasia Treated With Asfotase Alfa - Srivastava, Priya S (J Endocr Soc, 2021)
Background: Perinatal Hypophosphatasia (HPP) is a rare and lethal disorder associated with a 50–100% mortality rate, usually due to respiratory complications. HPP occurs due to a loss-of-function mutation in the ALPL gene, responsible for the function of tissue-nonspecific alkaline phosphatase (TNSALP). Clinically, HPP presents as a severe lack of bone mineralization leading to a rickets-like presentation. Clinical Case: A 4-month-old female presented from an outside hospital for the ongoing care of perinatal HPP. Prenatal scans with long-bone fractures raised concern for Osteogenesis imperfecta. However, alkaline phosphatase (ALP) at birth was <11 U/L, and vitamin B6 was elevated >250 ng/mL. Calcium, 25-OH vitamin D, and urine phosphoethanolamine were normal. A genetics panel for HPP confirmed two pathogenic autosomal recessive mutations on the ALPL gene. Treatment with asfotase alfa 3 mg/kg three times weekly was started on day two of life. The clinical course has been complicated by the need for mechanical ventilator support, seizure-event shortly after birth, recent EEG demonstrating epileptogenic potential in the bitemporal cortical regions now on treatment with Keppra, possible craniosynostosis with mild-to-moderate ventriculomegaly, and minimal grade 1 medullary nephrocalcinosis. Bone mineralization is monitored via skeletal surveys, and changes are measured using the Radiographic Global Impression of Change (RGI-C) and the Rickets Scoring Scale (RSS). After four months of asfotase alfa treatment, substantial progress in bone mineralization per RGI-C scoring has been noted, but RSS scoring still indicates severely low bone mineralization. ALP remains >3,000 U/L. Calcium, 25-OH vitamin D, and vitamin B6 are normal. Careful monitoring with weekly biochemical and urine profiles and monthly skeletal surveys, neuro assessments, and renal ultrasounds are ongoing. Conclusions: This clinical case demonstrates the improvement in bone mineralization with asfotase alfa, but the clinical course is slow and arduous. Despite the early initiation of asfotase alfa the patient’s bone mineralization remains severely low and is not in a safe range to proceed with G-tube, broviac, or tracheostomy placement. The current management goal is to maximize bone mineralization in preparation for the life-sustaining procedures mentioned above. With only a handful of surviving cases in the world, current long-term survival and outcomes for patients with perinatal HPP are unclear.